Deconstructing Insolvency: Challenging Inequities in Legal Protection - Husendro, Husendro (Nurani Hukum, 2024)
Indonesia's Bankruptcy Law (Law No. 37 of 2004) suffers from a rigid framework, often failing to provide balanced protection for creditors and debtors by neglecting the realities of business distress. This creates an urgent need for insolvency principles to help debtors avoid bankruptcy. The current system frequently leads to conflicts of norms when compared to the internationally recognized reorganization and rehabilitation frameworks of Chapters 11, 12, and 13 of the US Bankruptcy Code. This research addresses this disparity, offering a novel normative juridical analysis of primary and secondary legal data using quantitative methods. Our findings underscore the critical importance of adopting reorganization (restructuring and rehabilitation) mechanisms, mirroring the debtor-centric approach of the US Bankruptcy Code. Unlike the current asset-focused Indonesian law, rehabilitation under these international guidelines assesses a debtor's future income potential, offering a more equitable path to debt resolution and business recovery. This study contributes significantly by advocating for a reform of Indonesian bankruptcy law, proposing a shift towards a more flexible and balanced insolvency regime that prioritizes rehabilitation and economic revitalization over immediate liquidation.